Little White Rabbit - Henkes, Kevin (New York : Greenwillow Books, 2011)
As he hops along a little rabbit wonders what it would be like to be green as grass, tall as fir trees, hard as rocks, and flutter like butterflies.
Keywords: Rabbits -- Fiction; Animal babies -- Fiction